2023
DOI: 10.1136/jitc-2022-005714
|View full text |Cite
|
Sign up to set email alerts
|

T lymphocytes induce human cancer cells derived from solid malignant tumors to secrete galectin-9 which facilitates immunosuppression in cooperation with other immune checkpoint proteins

Abstract: BackgroundGalectin-9 is a member of the family of lectin proteins and crucially regulates human immune responses, particularly because of its ability to suppress the anticancer activities of T lymphocytes and natural killer cells. Recent evidence demonstrated that galectin-9 is highly expressed in a wide range of human malignancies including the most aggressive tumors, such as high-grade glioblastomas and pancreatic ductal adenocarcinomas, as well as common malignancies such as breast, lung and colorectal canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…Furthermore, we found that VISTA was preferentially expressed on TAMs in gastric cancer. Since previous studies reported VISTA could also be expressed by CD8 + T cells and cancer cells, 33 or expressed VISTA may be translocated onto the cell surface, where it contributes to suppression of T‐cell activity 34 . VISTA can also be shed off the cell surface and secreted (40 kDa soluble VISTA) 35,36 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we found that VISTA was preferentially expressed on TAMs in gastric cancer. Since previous studies reported VISTA could also be expressed by CD8 + T cells and cancer cells, 33 or expressed VISTA may be translocated onto the cell surface, where it contributes to suppression of T‐cell activity 34 . VISTA can also be shed off the cell surface and secreted (40 kDa soluble VISTA) 35,36 .…”
Section: Discussionmentioning
confidence: 99%
“…Considering that Gal-9 lacks a transmembrane domain ( 16 ), it’s unclear whether Gal-9 get released by other cells and subsequently binds to its receptor on NK cells or it is translocated from the cytosol of NK cells to their membrane. Gal-9 is ubiquitous and can be sourced from different immune, non-immune, and tumor cells, or apoptotic cells ( 24 , 25 , 47 ). Alternatively, Gal-9 presence could be subsequent to disease chronicity and persistent infection ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…IL-2 seems to be a potential AKNA-controlled factor whose implications in helper T-cell activation and cancer are relevant for the appropriate function of cells. Nonetheless, there exists evidence indicating that IL-2 is regulated by PI-3K/MAPK or PD-L1 [ 20 , 21 ], and thus these molecules could have a potential impact on AKNA-induced IL-2 effects. Whether AKNA is affected by such regulators remains unknown.…”
Section: Discussionmentioning
confidence: 99%